2023
DOI: 10.1021/acs.biomac.2c00877
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Immobilization on Sulfated Cellulose Nanocrystals

Abstract: Exploiting cellulose nanocrystals’ high aspect ratio and tailorable surface for immunological biosensors has been hindered by the relatively limited research on using commonly available sulfated cellulose nanocrystals (CNCs) for antibody immobilization and by the low hydrolytic stability of dried assemblies produced from sulfated CNCs. Herein, we report a reaction scheme that enables both hydrolytic stability and antibody immobilization through 3-aminopropyl-triethoxysilane and glutaric anhydride chemistry. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Some aggregates were large enough to distort cross-polarized optical microscopy images. Previous work showed that CNC-APTES aggregates became larger and more numerous with increasing concentration, which could result in less available surface area for further modification and nonuniform macroscale properties. The CNC and APTES concentrations used in this study were optimized by Nori, to achieve enough colloidal stability for further surface reactions …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some aggregates were large enough to distort cross-polarized optical microscopy images. Previous work showed that CNC-APTES aggregates became larger and more numerous with increasing concentration, which could result in less available surface area for further modification and nonuniform macroscale properties. The CNC and APTES concentrations used in this study were optimized by Nori, to achieve enough colloidal stability for further surface reactions …”
Section: Resultsmentioning
confidence: 99%
“…Based on a previously developed method, , the as-received CNC dispersion was added in an APTES plus solvent (water–ethanol, 80:20 v/v) mixture at a mass ratio of 1.8:1 after adjusting the pH to 4.0 with the addition of glacial acetic acid. It is noted that running the reaction with a higher APTES ratio increased aggregation, most likely due to APTES cross-linking the CNCs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their high surface-to-volume ratio, cellulose nanomaterials can be chemically modified to provide surface functionalization and overcome the limits related to their hydrophilic nature, thus broadening the range of materials to which they can be combined and expanding the application possibilities. 15 In this regard, oxidation treatments, such as TEMPO-mediated oxidation (via 2,2,6,6-tetramethylpiperidin-1yl-oxyl), can be used to introduce carboxylic acid moieties in CNCs, which in turn can support additional modification by binding with different biomolecules, such as amino acids, 26 peptides, 27 or antibodies, 28 thus fostering potential biomedical applications.…”
Section: Introductionmentioning
confidence: 99%